Surfactant protein D (SP‐D) deficiency is attenuated in humanised mice expressing the Met(11)Thr short nucleotide polymorphism of SP‐D: implications for surfactant metabolism in the lung. Issue 6 (23rd September 2013) - Knudsen, Lars; Ochs, Katharina; Boxler, Laura; Tornoe, Ida; Lykke‐Sorensen, Grith; Mackay, Rose‐Marie; Clark, Howard W.; Holmskov, Uffe; Ochs, Matthias; Madsen, Jens
Abstract: Surfactant protein D (SP‐D) is part of the innate immune system involved in lung homeostasis. SP‐D knockout mice show accumulations of foamy alveolar macrophages, alveolar lipoproteinosis and pulmonary emphysema. Three single nucleotide polymorphisms (SNPs) have been described in the coding sequence of the human SP‐D gene SFTPD . Clinical studies showed that the SNP SFTPD with a nucleotide change from A to C resulting in a Met to Thr substitution at position 11 in the protein (Met(11)Thr), is relevant. This study set out to create a humanised mouse model of the Met(11)Thr SNP. Transgenic mice lines expressing either Met(11) or Thr(11) SP‐D under the control of the ubiquitously expressed pROSA26 promoter in C57Bl/6 SP‐D deficient mice (DKO) was created. Both Met(11) (142 ± 52 ng mL −1 ) and Thr(11) (228 ± 76 ng mL −1 ) mice lines expressed human SP‐D at almost similar levels. According to the literature this was within the range of SP‐D levels found in wildtype (WT) mice (253 ± 22 ng mL −1 ). Met(11) or Thr(11) SP‐D in serum from transgenic mice bound maltose in a calcium‐dependent manner, and binding was inhibited in the presence of EDTA or maltose. Bronchoalveolar lavage showed for both transgenic mice lines complementation of the DKO phenotype by restoring cell counts, phospholipid levels and protein content back to WT levels. Cytospins of BAL pellet cells showed a resemblance to WT but both mice lines showed some foamy alveolar macrophages. The stereological analysis showed for none of the mice lines a complete abrogation of emphysematous alterations. However, both Met(11) and Thr(11) mice lines were partially reverted back to a WT phenotype when compared with DKO mice, indicating important effects on surfactant metabolism in vivo .